Modelling the cost-effective spatio-temporal allocation of conservation measures in agricultural landscapes facing climate change - Charlotte Gerling; Martin Drechsler; Klaus Keuler; Johannes A. Leins; Kai Radtke; Björn Schulz; Astrid Sturm; Frank Wätzold (ZBW - Leibniz Information Centre for Economics, 2021)
In agricultural landscapes, climate change has profound impacts on species that society aims to conserve. In response to climate change, species may adapt spatially (with range shifts) and temporally (with phenological adaptations), which may make formerly effective conservation sites and measures less effective. As climate change also has an impact on yields, opportunity costs of land use-based conservation measures may also change spatially and with respect to the timing of conservation measures. Due to these spatio-temporal modifications of the costs of conservation measures and their impacts on species, formerly cost-effective conservation sites and measures may no longer be so in a changing climate. We combine ecologicaleconomic modelling with climate science to investigate climate change-induced modifications of the timing and spatial allocation of cost-effective conservation measures. We apply our model to the case study of conserving the large marsh grasshopper on agricultural grasslands in the German federal state of Schleswig-Holstein. Comparing the periods 2020-2039 and 2060-2079, our model indeed indicates that climate change induces modifications in the costeffective spatial allocation of conservation measures and that measures which are adapted to phenological changes remain cost-effective under climate change.
Keywords: Q57; 330; climate-ecological-economic model; conservation planning; large marshgrasshopper; cultural landscapes; biodiversity conservation